Hypoxia Correlates With Poor Survival and M2 Macrophage Infiltration in Colorectal Cancer - Qi, Lina; Chen, Jiani; Yang, Yanmei; Hu, Wangxiong (Frontiers in Oncology, 2020)
Background: It is widely accepted that the oxygen level in tumor tissue is significantly lower than the adjacent normal tissue, thus termed hypoxia. Intratumoral hypoxia represents a major driving force in cancer progression, recurrence, metastasis, and decreased survival. Though multiple gene signatures reflect the complex cellular response to hypoxia have been established in several cancer types such as head and neck, breast, and lung cancers, the hypoxic panorama in colorectal cancer (CRC) remains poorly understood. Methods: A hypoxic signature constituted by a total of 356 genes, including canonical hypoxia-responsive ADM, ANGPTL4, CA9, and VEGFA, was established based on systemic literature search. A total of 1,730 CRC samples across four independent cohorts were used for nonnegative matrix factorization clustering and subtyping. Prognosis, molecular signatures, pathways, and tumor-infiltrating lymphocytes were compared between the subtypes. Results: CRCs mainly fell into two subgroups, one indicated as hypoxia and the other one designated as normoxia. Hypoxia was correlated with poor outcomes in CRC and will increase the risk of a subset of stage II patients to the level of normoxic stage III. Additionally, hypoxia was closely associated with activation of RAS signaling pathway independent of KRAS mutation. More M2 macrophage infiltration was another hypoxic marker indicated that subsets of patients with high M2 macrophages may benefit from macrophage-targeting therapy. Conclusions: These findings will facilitate the development of a hypoxia-oriented therapy strategy to enhance the treatment effect in the near future.